Foreigners' Rights to Work and Fair Labour Practices in South Africa: A Review of the South African Labour Legislation and Jurisprudence - Mangu, Andre (Southern African Public Law, 2020)
After several decades of apartheid rule, which denied human rights to the majority of the population on the ground of race and came to be regarded as a crime against humanity, South Africa adopted its first democratic Constitution in the early 1990s. The 1996 Constitution, which succeeded the 1993 interim Constitution, is considered one of the most progressive in the world. In its founding provisions, it states that South Africa is a democratic state founded on human dignity, the achievement of equality, the advancement of human rights and freedoms. The Constitution enshrines fundamental human rights in a justiciable Bill of Rights as a cornerstone of democracy. Unfortunately, in the eyes of a number of politicians, officials and lay-persons, the rights in the Bill of Rights accrue to South African citizens only. Xenophobia, which has been rampant since the end of apartheid, seems to support the idea that foreigners should not enjoy these rights. Foreign nationals have often been accused of posing a threat to South African citizens with regard to employment opportunities. In light of the South African legislation and jurisprudence, this article affirms the position of the South African labour law that foreign nationals are indeed protected by the Constitution and entitled to rights in the Bill of Rights, including the rights to work and fair labour practices.